The future of housing finance restructuring the U.S. residential mortgage market - Baily, Martin Neil (Brookings Institution Press, 2011)
"Evaluates the options open to policymakers as they reassess the federal government's role in the U.S. residential mortgage market and consider a new system that reduces risk in mortgage lending, maintains a limited government role, and gradually removes the government-sponsored enterprises (Fannie Mae and Freddie Mac) from the mortgage market"--Provided by publisher.